Effects of high-temperature, short-time pasteurization on milk and whey during commercial whey protein concentrate production - Joanna Haas; Bum Jin Kim; Zeynep Atamer; Chao Wu; David C. Dallas (Journal of Dairy Science)
ABSTRACT: Two pasteurization steps are often used in the preparation of whey protein concentrate (WPC) before evaporation into a dry product. The Pasteurized Milk Ordinance in the United States requires that raw bovine milk be pasteurized using a process that meets minimum heat treatment requirements to achieve reductions in pertinent microorganisms. In addition, WPC produced from USDA-approved plants must comply with CFR subpart B §58.809, which dictates that all fluid whey used in the manufacture of dry whey products shall be pasteurized before being condensed. These heat treatments are effective at inactivating the most thermally resistant bacterium, such as Coxiella burnetii; however, they can also alter milk proteins, inducing denaturation, aggregation, and reduced bioactivity. Though the impact of thermal treatments on whey proteins has been examined, the specific influence of 2 HTST pasteurization steps on the retention of proteins in WPC remains unknown. This study aimed to investigate the effect of commercial-scale HTST pasteurization of both raw milk and the resulting sweet whey on the products' overall protein profile. We analyzed 3 distinct batches of raw milk (RM) and the corresponding pasteurized milk (PM), resulting whey (RW), and pasteurized whey (PW) produced at commercial scale. Assessments of denaturation were conducted through solubility testing at pH 4.6 and hydrophobicity evaluation via anilinonaphthalene-1-sulfonic acid assay. Additionally, ELISA, PAGE, and liquid chromatography tandem MS (LC-MS/MS) were employed to compare the retention of key bioactive proteins before and after each HTST pasteurization step. The percentage of soluble whey protein decreased from RM to PM and from RW to PW, but no significant differences were observed via hydrophobicity assay. The ELISA revealed a significant reduction in key bioactive proteins, such as lactoferrin, IgA, and IgM, but not IgG, after HTST pasteurization of RM and RW. The PAGE and LC-MS/MS results revealed a significant decrease in the retention of lactoferrin and key milk fat globular membrane proteins, such as xanthine dehydrogenase oxidase/xanthine oxidase, lactadherin, and fatty acid binding protein. Additionally, xanthine oxidase activity was significantly reduced after HTST pasteurization of milk and whey. This research helps to identify the limitations of the current processing techniques used in the dairy industry and could lead to innovation in improving the retention of bioactive proteins.